The hive - Hornby, Gill (Little, Brown and Company, 2013)
It's the start of another school year at St. Ambrose. While the children are busy in the classroom, their mothers are learning sharper lessons. Lessons in friendship. Lessons in betrayal. Lessons in the laws of community, the transience of power and how to get invited to lunch. Beatrice, undisputed queen bee. Ruler, by Divine Right, of all school fundraising, this year, last year, and, surely, for many to come. Heather is desperate to volunteer, desperate to be noticed, desperate to belong. Georgie is desperate for a cigarette. Rachel is watching them all, keeping her distance. But soon to discover that the line between amused observer and miserable outcast is a thin one.